PRESS FREEDOM IN MOROCCO: a changing arena - Chafik, Ayoub; Iharchane, Omar (Brazilian journalism research, 2025)
ABSTRACT – This article studies the structure of the press in Morocco, as well as its changes in light of the rules of conflict between forces with contradictory interests, positions, and expectations vis-à-vis the press. We base this approach on an observation of the historical changes that have occurred in press legislation in Morocco, in the institutional framework regulating the press, and the productive dynamics of press platforms in terms of the fight for a professional and independent press. The historical approach to the conflict situation is very important because it will show that the Moroccan public space has witnessed moments of harmony, apprehension, and tension which brought its political and media spheres out of a state of coexistence, over short periods, to enter into conflict, by risking imprisonment, by arresting newspapers or by imposing custodial sanctions on journalists, or by imposing fines on newspapers that are disproportionate with regard to their turnover, or even by deciding to prevent journalists from practicing their profession. RESUMO – Este artigo estuda a estrutura da imprensa em Marrocos, bem como as suas mudanças, à luz das regras de conflito entre forças com interesses, posições e expectativas contraditórias face à imprensa. Baseamos esta abordagem na observação das mudanças históricas ocorridas na legislação de imprensa em Marrocos, no quadro institucional que regula a imprensa, bem como na dinâmica produtiva das plataformas de imprensa na luta por uma imprensa profissional e independente. A abordagem histórica da situação de conflito é muito importante porque mostrará que o espaço público marroquino testemunhou momentos de harmonia, apreensão e tensão que tiraram as suas esferas política e mediática de um estado de coexistência, durante curtos períodos, para entrar em conflito, arriscando a prisão, prendendo jornais ou impondo sanções de prisão a jornalistas, ou impondo multas aos jornais desproporcionais ao seu volume de negócios, ou mesmo decidindo impedir os jornalistas de exercerem sua profissão. RESUMEN – Este artículo estudia la estructura de la prensa en Marruecos, así como sus transformaciones, a la luz de las reglas del conflicto entre fuerzas con intereses, posiciones y expectativas contradictorias respecto a la prensa. Basamos este enfoque en la observación de los cambios históricos ocurridos en la legislación de prensa en Marruecos, en el marco institucional que regula la prensa, así como en la dinámica productiva de las plataformas periodísticas en su lucha por una prensa profesional e independiente. El enfoque histórico de la situación de conflicto es muy importante porque mostrará que el espacio público marroquí ha experimentado momentos de armonía, aprensión y tensión que han llevado a sus esferas política y mediática de un estado de coexistencia, durante cortos períodos, a entrar en conflicto, con riesgos de encarcelamiento, cierre de periódicos o la imposición de penas de prisión a periodistas, así como la aplicación de multas a los medios desproporcionadas en relación con su volumen de negocios, o incluso la decisión de impedir que los periodistas ejerzan su profesión. RÉSUMÉ – Cet article étudie la structure de la presse au Maroc, ainsi que ses mutations, à l’aune des règles du conflit entre des forces aux intérêts, positions et attentes contradictoires vis-à-vis de la presse. Nous appuyons cette démarche sur une observation des changements historiques survenus dans la législation de la presse au Maroc, dans le cadre institutionnel régulant la presse, ainsi que la dynamique productive des plateformes de presse au niveau de la lutte pour une presse professionnelle et indépendante. L’approche historique de la situation conflictuelle est très importante car elle montrera que l’espace public marocain a été témoin de moments d’harmonie, d’appréhension et de tension qui ont fait sortir ses sphères politique et médiatique d’un état de coexistence, sur de courtes périodes, pour entrer en conflit, en risquant l’emprisonnement, en arrêtant des journaux ou en imposant des sanctions privatives de liberté aux journalistes, ou encore en infligeant aux journaux des amendes disproportionnées par rapport à leur chiffre d’affaires, voire en décidant d’empêcher les journalistes d’exercer leur profession.